Evaluating Sharia-Based Marketing Strategies and Their Effect on Purchase Intention in Higher Education Enterprises - Triyawan, Andi; Alhasani, Irham Abied; Ismail, Nurizal (Business, Management & Accounting Journal (BISMA), 2025)
This study aims to analyze the influence of the sharia marketing mix on consumer purchase intention. The sharia marketing mix not only adopts conventional marketing principles but also emphasizes Islamic values based on honesty, justice, and blessings. A quantitative approach was employed by distributing questionnaires to consumers of products and services, and the collected data were analyzed using multiple regression to examine the effects of product, price, promotion, and distribution variables from a sharia perspective. The findings reveal that all sharia marketing mix variables have a positive and significant effect on consumer purchase intention, with sharia promotion identified as the most dominant factor. These results indicate that the implementation of sharia-compliant marketing strategies can enhance consumer trust, loyalty, and purchasing tendencies. This study is expected to provide practical contributions to the development of more effective sharia marketing strategies to remain competitive in the modern business era.